Prevalence of mcr-type genes among colistin-resistant Enterobacteriaceae collected in 2014-2016 as part of the INFORM global surveillance program. - Mark G Wise; Mark A Estabrook; Daniel F Sahm; Gregory G Stone; Krystyna M Kazmierczak (PLoS ONE, 2018)
A set of 908 clinically derived colistin-resistant Enterobacteriaeae isolates collected worldwide in 2014-2016 were screened for the presence of the plasmid-borne mcr-1, mcr-2, mcr-3, mcr-4 and mcr-5 genes. In total 3.2% (29/908) of the collection were positive for mcr, including 27 Escherichia coli, 1 Klebsiella pneumoniae and 1 Enterobacter cloacae. Twenty-four isolates possessed genes from the mcr-1 family, including the original mcr-1 (n = 22), as well as mcr-1.2 (n = 1) and mcr-1.5 (n = 1), which each differ from mcr-1 by encoding single amino acid variations. Genes from the mcr-3 family were found in isolates from Thailand, including mcr-3.1 (n = 3) and mcr-3.2 (n = 1). An E. coli isolated from a patient with a urinary tract infection in Colombia contained the recently discovered mcr-5. The full colistin-resistant collection was tested against a panel of antimicrobial agents with ceftazidime-avibactam and tigecycline exhibiting the highest activity.